The uncharted territory of host-pathogen interaction in tuberculosis - Ghoshal, Antara; Verma, Akanksha; Bhaskar, Ashima; Dwivedi, Ved Prakash (Frontiers in Immunology, 2024)
Mycobacterium tuberculosis (M.tb) effectively manipulates the host processes to establish the deadly respiratory disease, Tuberculosis (TB). M.tb has developed key mechanisms to disrupt the host cell health to combat immune responses and replicate efficaciously. M.tb antigens such as 19kDa lipoprotein, Hip1, and Hsp70 destroy the integrity of cell organelles (Mitochondria, Endoplasmic Reticulum, Nucleus, Phagosomes) or delay innate/adaptive cell responses. This is followed by the induction of cellular stress responses in the host. Such cells can either undergo various cell death processes such as apoptosis or necrosis, or mount effective immune responses to clear the invading pathogen. Further, to combat the infection progression, the host secretes extracellular vesicles such as exosomes to initiate immune signaling. The exosomes can contain M.tb as well as host cell-derived peptides that can act as a double-edged sword in the immune signaling event. The host-symbiont microbiota produces various metabolites that are beneficial for maintaining healthy tissue microenvironment. In juxtaposition to the abovementioned mechanisms, M.tb dysregulates the gut and respiratory microbiome to support its replication and dissemination process. The above-mentioned interconnected host cellular processes of Immunometabolism, Cellular stress, Host Microbiome, and Extracellular vesicles are less explored in the realm of exploration of novel Host-directed therapies for TB. Therefore, this review highlights the intertwined host cellular processes to control M.tb survival and showcases the important factors that can be targeted for designing efficacious therapy.